TRANSCRANIAL DIRECT CURRENT STIMULATION FOR ANXIETY: CURRENT EVIDENCE AND CONSIDERATIONS FOR CLINICAL PRACTICE - Lucas Caseri Câmara; Matheus Hissa Lourenço Ferreira (Artefactum - revista de estudos interdisciplinares, 2026)
Introduction: Transcranial direct current stimulation (tDCS) has been investigated as a noninvasive strategy for modulating neural circuits involved in anxiety, but its clinical efficacy and therapeutic parameters remain uncertain. Objective: To critically review the available evidence on the use of tDCS for anxiety symptoms and anxiety disorders, focusing on efficacy, cortical targets, electrode montage and polarity, intensity, session duration and number, neurobiological mechanisms, combination with psychological interventions, durability, predictors of response, and safety. Methods: A narrative review of the literature was conducted using PubMed searches and reference tracking. Systematic reviews, meta-analyses, and randomized clinical trials were prioritized; experimental and mechanistic studies were included when relevant to understanding stimulation effects. Results: The literature suggests a potential reduction in anxiety symptoms, but with substantial heterogeneity across diagnoses, populations, and stimulation protocols. The dorsolateral prefrontal cortex is the most extensively investigated target, and protocols using 2 mA, sessions of approximately 20 minutes, and repeated applications are common, although none of these parameters has been established as optimal. Mechanistic studies indicate modulation of frontolimbic circuits, amygdala reactivity, threat processing, and fear extinction. Combining tDCS with psychotherapy has shown promising results in some studies, but findings remain inconsistent. tDCS has a favorable safety profile, with mostly mild and transient adverse events. Conclusion: tDCS is an investigational strategy of interest for anxiety, but current evidence does not support a universal therapeutic protocol. Larger and more standardized studies are needed to identify which patients and clinical contexts are most likely to benefit.